Two new species of the sharpshooter genus Oragua Melichar, 1926 from Southeastern Brazil (Hemiptera: Cicadellidae: Cicadellini) - Mejdalani, Gabriel; Silva, Cristiane M. F. Da; Takiya, Daniela M. (Zootaxa, 2016)
Two very similar new species of Oragua Melichar, 1926, O. linnavuorii sp. nov. and O. flavolineata sp. nov., are described and illustrated from the Atlantic Forest of Southeastern Brazil (Mantiqueira mountain range). The new species share the presence of a large dentiform process located posteroventrally on the male pygofer, a unique feature within the genus. They can be distinguished from each other by the paraphyses with a pair of elongate, slender asymmetrical rami in O. linnavuorii and with two pairs of short, spiniform apical processes in O. flavolineata. The male of O. linnavuorii is macropterous but the female is submacropterous and thus smaller than the former when specimens are measured from the apex of the crown to the tips of the forewings at rest. The female of O. flavolineata is not known. Male holotypes are deposited in DZRJ. A key to males of the five Oragua species recorded from Southeastern Brazil is provided [O. maculifera Young, 1977, O. discoidula (Osborn, 1926), O. triplehorni Young, 1977, O. linnavuorii, and O. flavolineata]. The superficially similar genera Oragua and Aguana Melichar, 1926 are briefly compared.